Analisis Deret Waktu Aktivitas Communication Log pada Sistem Penerimaan Mahasiswa - Wulandari, Kristina (Fakultas Teknologi Informasi, 2025)
Digital communication analysis within university admission systems plays a crucial role in understanding the effectiveness of interactions between prospective students and the integrated admission platform. This study aims to analyse the time series patterns of communication activities recorded in the admission system’s communication logs from two years. A quantitative descriptive time series approach was employed, focusing on the frequency of activities based on daily, weekly, and hourly intervals, as well as calculating the time differences between logs to measure user interaction intensity and response speed. The results indicate a significant increase in communication activity prior to the enrolment period, with the highest frequency observed in Week 41 of 2021 and Week 3 of 2022. The analysis of time differences between logs reveals noticeable variations in user behaviour, where some applicants demonstrated long interaction gaps, while others exhibited high and continuous system engagement. These variations highlight differences in user involvement levels during the digital communication process within the admission stages. This study contributes to a deeper understanding of user interaction patterns in integrated admission systems and serves as a basis for developing strategies to enhance user experience through optimized notifications, adaptive system responsiveness, and interface designs tailored to user behavior.